The time is now: Achieving FH paediatric screening across Europe - The Prague Declaration - Bedlington, Nicole; Abifadel, Marianne; Beger, Birgit; Bourbon, Mafalda; Bueno, Héctor; Ceska, Richard; Cillíková, Kristýna; Cimická, Zdenka; Daccord, Magdalena; de Beaufort, Carine; Dharmayat, Kanika I; Ference, Brian A; et al. (GMS health innovation and technologies, 2022)
Familial hypercholesterolaemia (FH) is the most common inherited metabolic disorder characterized by high cholesterol and if left untreated leads to premature cardiovascular disease, such as heart attacks. Treatment that begins early in life, particularly in childhood, is highly efficacious in preventing cardiovascular disease and cost-effective, thus early detection of FH is crucial. However, in Europe, less than 10% of people living with FH are diagnosed and even less receive life-saving treatment. The Prague Declaration is a call to action for national and European Union policymakers and decision-makers and a result of the Czech EU Presidency meeting on FH Paediatric Screening (early detection of inherited high cholesterol) at the Czech Senate in Prague on 6th September 2022. It builds on a considerable body of evidence which was discussed at the Technical Meeting under the auspices of the Slovenian EU Presidency in October 2021. The Prague meeting addressed the outstanding barriers to the systematic implementation of FH paediatric screening across Europe. In this article, we present the key points from the Prague meeting and concrete actions needed to move forward.
Keywords: familial hypercholesterolaemia; screening; declaration; EU; EU best practice; Europe; FH; cardiovascular health; children; implementation; public health; health systems; cardiovascular disease; prevention; CVH; CVD